Peran Psikologi Tasawuf Mengenai Kesehatan Mental dan Spiritualitas Generasi Z Pada Era Digital - Mashita Putri Waluyojati; Darsista Irma Swari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to explore the role of Sufism in overcoming the weak mental health and spirituality of generation Z in the digital era. The research method uses qualitative research and is descriptive, namely library research by examining and studying theories from various data sources from journals, books and previously existing research so that it is relevant to the title of this research. Based on the results of this research, it shows that digital technology can disrupt social interactions and spiritual abilities, but also offers opportunities to increase religious knowledge and moral awareness through easy access to information. Sufism, with concepts such as takhalli and tazkiyah al-nafs, can help individuals cleanse their hearts, develop noble qualities, and find inner peace. Supported by easy access to information and interaction, individuals are more aware of mental health. However. The use of digital technology also has a negative impact on mental health, namely individuals experience anxiety, stress, depression and addiction to using digital technology. Therefore, Sufism has great potential in strengthening the spirituality and mental health of Generation Z in the digital era.